Rizal and the development of national consciousness - Romero, Ma. Corona S.; Sta. Maria, Julita R. ;Santos, Lourdes Y. (Quezon City, Philippines : Katha Publishing Co, Inc., 2006)
It's a prepared a textbook for the course on the life, works and writings of Jose Rizal in accordance with the requirements of the Rizal Law.
1. Introduction : Significant contemporary insights -- 2. A Panoramic Survey -- 3. Birth of A Filipino National consciousness -- 4. Development of Rizal's Nationalism -- 5. Nationalism in the novels -- 6. Idealism in the poetry -- 7. Ideology in the Prose -- 8. Rizal's concepts of nation building -- 9. The relevance and validity of Rizal's concepts -- 10. Tribute to a man and a hero -- 11. tribute to our people and leaders heroic leadership for the 21st Century
Includes bibliographical references and index.
Keywords: RIZAL, JOSE P